Antibiotics use and ethnoveterinary practices in pig farming: an insight from federal capital territory, Nigeria - Jones Soladoye Akinbobola; Olaoluwa Ayeoribe Kumuyi; John Abiola Olusoji; Jude Nduka Omeje; Theophilus Aderemi Dare; Kelvin Olutimilehin Jolayemi (BMC Veterinary Research)
Abstract Pig farming is a crucial component of global livestock production, contributing to food security, economic growth, and rural livelihoods. However, the misuse of antibiotics in livestock farming has raised serious concerns about antimicrobial resistance (AMR), a global health crisis threatening both human and animal health. Ethnoveterinary medicine remains widely practiced but lacks scientific validation and integration into conventional veterinary systems. This study assessed the demographic characteristics, antibiotic use, and ethnoveterinary practices among pig farmers in the Federal Capital Territory (FCT), Nigeria. A cross-sectional survey of 40 pig farmers was conducted using structured questionnaires, and data were analyzed using descriptive statistics and chi-square tests for association. Results showed that pig farming in FCT is male-dominated (67.5%), with most farmers (52.5%) aged 41–60 years and having only primary education (52.5%). Antibiotic use was widespread, 90% of farmers administered antibiotics, with oxytetracycline, penicillin, and amoxicillin being most commonly used. Self-administration was common (72.5%), and a significant association was found between antibiotic administration and frequency of use (χ 2 = 28.96, df = 2, p = 0.00). Farms with local pig breeds exhibited higher antibiotic use (χ 2 = 11.11, df = 2, p = 0.00). Ethnoveterinary medicine was practiced by 50% of farmers, with significant associations between its use and education level (χ 2 = 17.98, df = 6, p = 0.00). There is an urgent need for antimicrobial stewardship, improved veterinary education, and standardized ethnoveterinary medicine integration. Addressing these issues may support sustainable livestock production and AMR mitigation in similar low-and middle-income settings. These findings add to the understanding of antimicrobial practices in localised settings which cumulatively influence the global AMR burden.